Variation in quality traits of different seed sizes of groundnut: Variation in quality traits of different seed sizes of groundnut - M K MAHATMA; L K THAWAIT; AMAN VERMA; NARENDRA KUMAR; SUSHMITA; A L SINGH (Journal of Oilseeds Research, 2020)
Groundnut is an energy rich oilseed and food crop. There is no information on quality traits of different seed sizes of a same groundnut verity. Therefore, in present investigation seven groundnut varieties i.e. Girnar 2, Girnar 3, GJG 9, GJG22, GG 20, KDG 128 and TG 37A were used to find out variations in quality traits of different seed sizes of groundnut. Small seed of groundnut possessed higher content of soluble sugars and protein while bold seeds had higher oil content. Oleic acid content was higher in bold seeds while linoleic acid was higher in smallseeds.